2015
DOI: 10.2215/cjn.10141014
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Molecular Characterization of Patients with Heterozygous Mutations in Wilms Tumor Suppressor Gene 1

Abstract: Background and objectives The Wilms tumor suppressor gene 1 (WT1) plays an essential role in urogenital and kidney development. Genotype/phenotype correlations of WT1 mutations with renal function and proteinuria have been observed in world-wide cohorts with nephrotic syndrome or Wilms tumor (WT). This study analyzed mid-European patients with known constitutional heterozygous mutations in WT1, including patients without proteinuria or WT.Design, setting, participants & measurements Retrospective analysis of g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
56
2
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 60 publications
(66 citation statements)
references
References 30 publications
1
56
2
2
Order By: Relevance
“…These data are supported by studies on wt1 heterozygous mice indicating that wt1 -heterozygosity predisposes the development of proteinuria and increased plasma levels of urea and creatinine leading to glomerular sclerosis later in life [12]. Lehnhardt et al [5] recently reported from a cohort of 53 patients that constitutional heterozygous WT1 mutations neither cause the full syndromal picture of DDS or FS nor a NS in all patients. Our patient was diagnosed with proteinuria in early adulthood, and her renal function is not impaired at 38 years, which is an unusual manifestation of a WT1 -associated nephropathy.…”
Section: Discussionmentioning
confidence: 82%
See 4 more Smart Citations
“…These data are supported by studies on wt1 heterozygous mice indicating that wt1 -heterozygosity predisposes the development of proteinuria and increased plasma levels of urea and creatinine leading to glomerular sclerosis later in life [12]. Lehnhardt et al [5] recently reported from a cohort of 53 patients that constitutional heterozygous WT1 mutations neither cause the full syndromal picture of DDS or FS nor a NS in all patients. Our patient was diagnosed with proteinuria in early adulthood, and her renal function is not impaired at 38 years, which is an unusual manifestation of a WT1 -associated nephropathy.…”
Section: Discussionmentioning
confidence: 82%
“…The WT1 mutation c.1372C>T (p.Arg458*) found in our patient results in truncation of the protein. This mutation has already been described as disease causing by others [5,6,8,9,10] and arginine at this position is highly conserved in evolution, which makes the pathogenicity of the mutation very likely.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations